Natureza, políticas públicas e (re)ordenamento do espaço: interfaces das políticas ambientais em Sergipe - Fontenele, Ana Consuelo Ferreira (2013)
Our challenge was to consider the extent to which the environmental issue as a current problem involves the relationship between society and nature, because this relationship appears in the geographical analysis of their inseparability. From this context, we builded the theory that the relationship between society and nature in geography presents itself as the key to understanding environmental policy in the state of Sergipe, while understanding the contradictory relations engendered in the capitalist economy. Therefore, we present the core objective, a critical analysis of the process of formation and implementation of environmental policies in Brazil, as well as the government in Sergipe establishing its environmental policy from the standards set by the Union. The research was guided by the geographical knowledge in relation to the normative positions of the dialectical method adopting a course of theoretical abstraction, which equips the way they treat the relationship between the abstract and the concrete, and operates the notion of spaciousness as not only actively produced, but also an active moment in the social process. In addition to the documentary analysis, empirical data collected in field visits were also used, which is the process of territorial actions directed or not, by the state instituted environmental policies. For this purpose a cutout of the space planning of public policies embodied in the territory of the Great Aracaju was made. In this dimension all objectives that led to this thesis were gestated from the hypothesis that environmental policies are territorial, ie they are state actions that promote the reorganization of the national space preparing it for new specializations. It was tried to contextualize the "environmental issue" in the context of the internationalization of the capital, focusing on the role of international organizations in the formulation of environmental policies and the development of public policies, analyzing the role of the state in implementing policies the directly affects the environmental issue that reflects the quality of life of the population as an explanatory pattern of the expansion of capital in different scales, local / national / global. It was noted the important role of science and technology in the appropriateness of the environment for economic growth ruled in the rational instrumental technique with dialogue between the organized population and the social organization for the dissemination of sustainable development. It was concluded that the environmental policy based on sustainable development has nature and community as factors of production subsumed to the capital, with hegemonic discourse and practices of domination, which they conducted in the rhetoric of public environmental policy discourses in everyday life partnerships (NGOs, Foundations, Institutes, etc..) in postures participatory local community, as well as the permeability for democratic relations.